2017
DOI: 10.1016/j.avsg.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Oxidative Stress and Hypoxia Inducible Factor-1 Expression during Arteriovenous Fistula Maturation

Abstract: Background The poor clinical results that are frequently reported for arteriovenous fistulae (AVF) for hemodialysis are typically due to failure of AVF maturation. We hypothesized that early AVF maturation is associated with generation of reactive oxygen species and activation of the HIF-1 pathway, potentially promoting neointimal hyperplasia. We tested this hypothesis using a previously reported mouse AVF model that recapitulates human AVF maturation. Methods Aortocaval fistulae were created in C57Bl/6 mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 35 publications
5
39
0
Order By: Relevance
“…Oxidative stress is known to stabilize HIF‐1α even under normoxic conditions (Kim & Byzova, ; Sadaghianloo et al., ; Zhou et al., ). Accordingly, HIF‐1α protein was detectable in higher amounts in aortae of 9‐month‐old WT mice compared to age‐matched Cc1 −/− mice, whereas mRNA expression was similar indicating protein stabilization (Figure e; ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is known to stabilize HIF‐1α even under normoxic conditions (Kim & Byzova, ; Sadaghianloo et al., ; Zhou et al., ). Accordingly, HIF‐1α protein was detectable in higher amounts in aortae of 9‐month‐old WT mice compared to age‐matched Cc1 −/− mice, whereas mRNA expression was similar indicating protein stabilization (Figure e; ).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, 4‐HNE, a stable lipid peroxidation product indicative of oxidative stress, was more abundant in aortae of WT mice. Increased oxidative stress in 9‐month‐old WT mice is of special interest, because it was shown that oxidative stress stabilizes HIF‐1α even under normoxic conditions (Kim & Byzova, ; Sadaghianloo et al., ; Zhou et al., ) and HIF‐1α mediates VEGF gene transcription (Shibuya, ). Indeed, the presence of HIF‐1α protein was higher in aortae of 9‐month‐old WT mice compared to Cc1 −/− mice, whereas mRNA expression was not different.…”
Section: Discussionmentioning
confidence: 99%
“…While the expression of OPN has been shown to be increased during early AVF maturation 54 or throughout maturation 34 under hypoxic conditions, 44 none of the three cell lines forming the three layers of the artery and vein walls expressed iOPN or sOPN.…”
Section: Discussionmentioning
confidence: 96%
“…Even though up‐regulation of OPN in hypoxia has been shown to be dependent or independent of HIF‐1 regulation, OPN expression is enhanced under hypoxia through different mechanisms, leading to co‐expression with VEGF . Moreover, we reported that the oxidative stress generated during early maturation of an AVF stabilized the HIF‐1α protein and thus activated HIF‐target genes such as Vegf‐A , Nox‐2 and Ho‐1 …”
Section: Introductionmentioning
confidence: 93%
“…In particular, NOX2 is implicated in endothelial cell migration [ 283 ] and NOX1, NOX4, and NOX5 are implicated in angiogenesis and neovascularization [ 284 ]. NADPH oxidase may be activated by different proangiogenic factors [ 285 ], including VEGF [ 286 ], and in turn can modulate the release of different angiogenesis-related factors, including VEGF-A [ 287 ], hypoxia-induced factor 1a (HIF-1a) [ 288 ], and matrix metalloproteinases (MMPs) [ 289 , 290 ].…”
Section: Nadph Oxidase Upregulation and Vascular Diseasementioning
confidence: 99%